PILIHAN RASIONAL MASYARAKAT KELURAHAN KUBU, KABUPATEN BANGLI MENJADI PEKERJA MIGRAN INDONESIA - Utama, I Kadek Wahyu; Suryani, Ni Gusti Ayu Putu; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI: SOROT, 2025)
This study aims to analyze the rational choices made by the people of Kubu Subdistrict, Bangli Regency, in becoming Indonesian migrant workers (PMI). Working abroad is often seen as a solution by the community amidst the challenges of securing employment domestically. Currently, Indonesia is one of the highest labor-sending countries in Southeast Asia. Various benefits that can be gained serve as motivations for individuals to choose to become PMIs. However, it is undeniable that the risks and challenges involved are not easy to face. This research uses a qualitative approach with a descriptive-explanatory method. The theoretical framework employed in this study is James S. Coleman's rational choice theory. The findings of this study show that there are several motivations that drive the people of Kubu Subdistrict to become PMIs, including environmental, economic, and social factors. The PMIs in Kubu Subdistrict are aware of and have directly experienced the risks and challenges involved, yet the presence of a supportive environment (family and village officials) has strengthened their decision to continue working abroad. After working as PMIs for some time, many changes have occurred in their lives. These changes include improvements in the economic, social, and lifestyle aspects, as well as cultural transformations. The presence of PMIs has also had an impact on Kubu Subdistrict, particularly in supporting village development through financial contributions. It is recommended for Kubu sub-district residents who will become PMI to improve their skills so that they can be more competitive in the destination country, so that they can get higher salaries and positions. Keywords: Rational Choice, Indonesian Migrant Workers, Motivation, Change